Proceedings of the 2014 International Conference on Mechatronics, Electronic, Industrial and Control Engineering 2014
DOI: 10.2991/meic-14.2014.237
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Design of A Modular Quadruped Robot - Xdog

Abstract: This article presents the mechanical design of a modular quadruped robot, named XDog. The leg mechanism of XDog has coplanar hip joints with the leg apart from the body to increase the motion range of the hip joint. Gear pair is used to drive each joint to promise high motion accuracy and compact assembling. Based on the leg mechanism and driving type, only one actuator is mounted on the leg with others in the torso to reduce the mass of the leg. Moreover, the leg design is modularized in a bilateral way, maki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The legs are entirely under the body, not the side. The design imitates mammalian structure, which is more conducive to the realization of the small ground occupation and strong load-bearing capacity [27]. The robot has a 2DOF platform with a USB camera, which can monitor a wide range of video images.…”
Section: Control Systemmentioning
confidence: 99%
“…The legs are entirely under the body, not the side. The design imitates mammalian structure, which is more conducive to the realization of the small ground occupation and strong load-bearing capacity [27]. The robot has a 2DOF platform with a USB camera, which can monitor a wide range of video images.…”
Section: Control Systemmentioning
confidence: 99%
“…The BigDog quadrupeds (Raibert et al, 2008) developed by the Boston Dynamics, Inc., is a renowned example of walking robots built for outdoor applications, whose design is inspired by the skeleton of mammals. The StarlETH (Hutter et al, 2012), LittleDog (Shkolnik et al, 2010), XDOg (Xie et al, 2014), MIT Cheetah (Seok et al, 2013), IIT HyQ (Semini et al, 2011) and Cheetah-cub (Spröwitz et al, 2013) are other examples of quadrupeds motivated by the mammalian morphology. Alternative design of the robot legs is inspired by the leg structure of insects and arachnids such as spider (Ho et al, 2007;Gasparetto et al, 2008), examples of which can be found in the design of TITAN quadruped (Kato and Hirose, 2001), LAVA (Zielinska and Heng, 2003), LAURON V (Roennau et al, 2013), PUT Hexapod Robots (Belter et al, 2015), MRWALLSPECT-III (Kang et al, 2003), and MiniQuad I (Chen et al, 2008).…”
Section: Introductionmentioning
confidence: 99%